The Nucleator - Alkan, I.; Altun, G.; Kaplan, S. (Nova Science Publishers, Inc., 2024)
It is essential to accurately estimate structures' geometric properties in biological studies. Although cell volumes, sizes and shapes vary depending on age or the chemicals used in some methods, the gold standards underlying stereological analysis ensure that the data obtained are close to real values. Some specific diseases or practices require particular volumetric analyses. The nucleator method helps to obtain very effective results, especially in studies in which it is important to obtain volumetric data for cellular components or specific cells. This method, performed by considering the intersections of lines issued from a specific point, has many areas of application. This chapter describes the nucleator method, some stereological techniques being briefly mentioned, and its areas of application through previous studies in the literature. © 2024 Nova Science Publishers, Inc. All rights reserved.
Keywords: Axonal Diameter; Cell Volume; Nucleator; Stereology; Volume Estimation